- A negative number means loss and when we add two losses then the sum represents more loss.
- A positive number means gain and when we add two gains then the sum represents more gain.
- To add two integers having same signs:
- Ignore the signs.
- Find the sum of the given numbers.
- The answer will have the same sign of the numbers.

**For example:** We want to add two negative numbers, \(-5\) and \(-15\).

\(-5+(-15)=-20\)

The answer is \(-20\).

**Note:** We can add the integers just like the whole numbers and keep the sign same.

- We can add the integers with different signs.

Steps to add integers having different signs:

- Ignore the signs.
- Find the difference of the given numbers.
- The answer will have the sign of the greater number.

**For****example:**Add \(-9\) and \(3\).

\(-9+3=\Box\)

- First, ignore the sign and find the difference of \(9\) and \(3\).

\(9-3=6\)

- Now, \(6\) will have the sign of the greater addend.

\(9\) is greater than \(3\).

So, the sum will have the sign same as \(9,\) i.e. '–'

Thus, \(-9+3=-6\)

**Example:**

\(-15+3=-12\)

\(12+(-7)=5\)

\(-5+2=-3\)

- We can subtract the integers having same signs.
- Follow the given steps to subtract the integers:

**Step 1:** Look at the integer being subtracted.

**Step 2:** Take the opposite of that integer (which is being subtracted).

**Step 3:** Add the opposite to the first integer.

**For example:** Subtract \(-9\) from \(-15\).

\(-15-(-9)=\Box\)

- The integer being subtracted is \(-9\), i.e. negative.

Opposite of \(-9\) is \(9\).

- Now, add \(-15\) and \(9\).

Thus, \(-15+9=-6\)

**Examples:**

- \(-8-(-4)=-4\)
- \(7-12=-5\)
- \(-20-(-10)=-10\)

- We can subtract integers with different signs.
- Follow the given steps to subtract the integers:

**Step 1:** Look at the integer being subtracted.

**Step 2:** Take the opposite of that integer (which is subtracted).

**Step 3:** Add the opposite to the first integer.

**For example:**Subtract \(2\) from \(-5\).

\(-5\,-2=\Box\)

- The integer being subtracted is \(2\), i.e. positive.
- Opposite of \(2\) is \(-2\).

Now, add \(-2\) to \(-5\).

\(-5+(-2)=-7\)

**Examples:**

- \(70-(-30)=100\)
- \(-15\,-45=-60\)
- \(55-(-25)=80\)